Edukasi Optimalisasi Produksi Kambing Perah Berbasis Kambing Peranakan Etawa Di Desa Aikmual Kecamatan Praya Kabupaten Lombok Tengah - Ica Ayu Wandira; Muhammad Dohi; I Nyoman Sadia; Ine Karni; Aminurrahman; Eva amalia Pratiwi (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service activity aimed to improve farmers’ understanding of optimizing Peranakan Etawa (PE) goats as dairy goats in Aikmual Village, Praya District, Central Lombok Regency. The activity involved 22 PE goat farmers and was carried out through socialization, participatory discussions, problem identification, and the formulation of follow-up recommendations together with the Livestock Office of Central Lombok Regency. The results showed that the farmers had experience in milking goats and basic skills in processing milk into mozzarella cheese, soap, and cosmetic products. However, business development still faces several constraints, including low selling prices for live goats, suboptimal milk production, poor recording of individual milk production, limited genetic quality, and inadequate market access. This activity encouraged farmers to maintain productive does, maximize milk production, record milk yields, diversify products, and strengthen marketing through institutional cooperation and potential market networks. Support from the local government is needed to provide superior breeds, processing equipment, technical assistance, and marketing facilitation so that PE goats can be developed as a basis for goat milk businesses and derivative products.